REGENERATIVE DISCOURSES IN CONTEMPORARY AFRO-BRAZILIAN WOMEN WRITERS - Afolabi, Niyi (fólio - revista de letras, 2019)
Drawing on James Scott’s idea of “hidden transcripts” in Domination and the Arts of Resistance, this study theorizes on progressive hypothetical discursive sites as moving from the continuum of the harsh slave master to the site of the free black among friends and family. Instead of the fear of articulation or the need for masking that operates in the public transcript frame, the alternating hidden transcript frame suggests a less explicit fear of articulation in the face of oppression. In addition to highlighting recent works on issues of gender, identity, and citizenship in Brazil, this essay argues that a new wave of regenerative discourses is emerging among Afro-Brazilian women writers however few and far between. These works demonstrate conscious regenerative acts from the viewpoints of rejection of victimhood.